Developing Seasonal Operation for Water Table Management in Tidal Lowland Reclamations Areas at South Sumatera, Indonesia - Momon Sodik Imanudin; Mustika Edi Armanto; Robiyanto Hendro Susanto (UNIVERSITY OF LAMPUNG, 2011)
The objective of the study was to develop the water management operational plan at tertiary blocks for the growth of rice and corn. Study was conducted at reclaimed tidal lowland area which was located at Primer 10, Delta Saleh. This area was classified as a C-typhology land (dry). The methods of the study were survey, field measurements, computer simulation, and field action research. Study stages were consisted of survey and monitoring, water status evaluation, water management scenarios design, model simulation, and model adaptation. Computer model of DRAINMOD had been used to estimate the water table status and to design water table control operation at tertiary blocks. Simulation results showed that the model worked properly which was indicated by root mean square error of 1.45 cm, model efficiency of 0.97, and correlation coefficient of 0.84. Model adaptation for dry land condition (C-typhology) showed that the best scenario was land utilization pattern of rice-corn. This paper presented monthly water management operational plan for rice crop in first cropping season (CS1) during November-February period and for corn crop in second cropping season (CS2) during May-August period. Results of computer simulation and field study showed that the main objective of water management in this area was water retention in combination with land leaching.